Daya Antibakteri Ekstrak Gum Arabic Baluran terhadap Pertumbuhan Porphyromonas gingivalis - Aprilia Wahyu Isdiyanto (Fakultas Kedokteran Gigi, 2025)
Porphyromonas gingivalis is a bacterium that plays an important role in the course of periodontal disease. Periodontal disease that is not treated properly will cause serious problems in the oral cavity to tooth loss. Prevention and treatment include plaque control using mouthwash containing antibacterials. Gum Arabic extract contains active compounds such as polyphenols, flavonoids, and tannins that have potential as antibacterials. The purpose of this study was to determine the antibacterial power of Baluran Gum Arabic extract at concentrations of 12,5 mg/ml, 25 mg/ml, 50 mg/ml, and 100 mg/ml in inhibiting the growth of P. gingivalis. Gum Arabic Baluran extracts with concentrations of 12,5 mg/ml, 25 mg/ml, 50 mg/ml, 100 mg/ml were prepared by extracting Gum Arabic Baluran by sonication method and serial dilution. The antibacterial test was performed by disc diffusion method using MHA media that had been inoculated with P. gingivalis. The zone of inhibition was seen around the disc paper with significant differences between sample groups. The zone of inhibition of Gum Arabic Baluran extract was largest at a concentration of 100 mg/ml at 16.89 + 0.14 mm and smallest at a concentration of 12,5 mg/ml at 0.00 + 0.00 mm. It can be concluded that Gum Arabic Baluran extract has antibacterial power that can inhibit the growth of P. gingivalis with the most effective concentration is 100 mg/ml
Entry oleh Arif 2026 Maret 26
Keywords: Antibacterial; Gum Arabic Extract; Porphyromonas Gingivalis